2006
DOI: 10.1088/0960-1317/16/3/001
|View full text |Cite
|
Sign up to set email alerts
|

Sharp beveled tip hollow microneedle arrays fabricated by LIGA and 3D soft lithography with polyvinyl alcohol

Abstract: This paper describes a fabrication process of hollow microneedle arrays with a sharp beveled tip for transdermal drug delivery. A master is fabricated through a double deep x-ray lithography process. First, a polymethylmethacrylate (PMMA) sheet is exposed to produce single PMMA parts with a sawtooth profile. The tip angle of each tooth determines the final tip angle of the microneedles. The PMMA parts are assembled and glued on a conductive substrate and then exposed through a second x-ray mask containing an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 14 publications
(15 reference statements)
0
83
0
Order By: Relevance
“…However, it is realized that since the first fabrication of microneedles a large variety of microneedle distribution have been proposed such as square (Ji et al, 2006;Kim and Lee, 2007), hexagonal (Matriano et al, 2002;Widera et al, 2006), triangular (Perennes et al, 2006) and rectangular (Park et 90 al., 2005). Aggarwal and Johnston (2004) investigated the influence of various patterns (e.g., square, rectangular, etc) on buckling force, bending force and bending stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is realized that since the first fabrication of microneedles a large variety of microneedle distribution have been proposed such as square (Ji et al, 2006;Kim and Lee, 2007), hexagonal (Matriano et al, 2002;Widera et al, 2006), triangular (Perennes et al, 2006) and rectangular (Park et 90 al., 2005). Aggarwal and Johnston (2004) investigated the influence of various patterns (e.g., square, rectangular, etc) on buckling force, bending force and bending stress.…”
Section: Introductionmentioning
confidence: 99%
“…The methods that have been adopted for microneedle fabrication include wet etching, deep reactive ion etching (DRIE) (Teo et al, 2005), microinjection moulding (Sammoura et al, 2007), isotropic etching, isotropic etching in combination with deep etching and wet etching respectively, dry etching, isotropic and anisotropic, photolithography, thin film deposition (Moon & Lee, 2003), laser cutting (Martanto et al, 2004), and inclined LIGA process (Perennes et al, 2006). Studies have shown that factors such as microneedle geometry, coating depth on solid microneedle and skin thickness affect the drug delivery efficiency using microneedles (Al-Qallaf et al, 2009a;2009b).…”
Section: Microneedles Manufacturingmentioning
confidence: 99%
“…15) are manufactured based on etching methods used by the microelectronics industry to create arrays of micron-sized needles [214,215]. The majority of studies to date have used silicon or metal MNs, although devices have also been made from dextrin [216,217], glass [218], maltose [219,220], and various polymers [221][222][223][224]. MNs can be made of varying length, as short as 25 m and as long as 2000 m. In addition, base diameter of the needle and needle density can also be altered.…”
Section: Microneedle Facilitated Drug Deliverymentioning
confidence: 99%